A decade of growth hormone treatment in girls with Turner syndrome in the UK - Betts, P (BMJ Group, 1999)
Fifteen per cent of children treated with growth hormone (GH) are receiving treatment for Turner syndrome, but few results are available on final height in the UK. In this study, data were obtained from the UK KIGS database for 485 girls with Turner syndrome who were treated from 1986, allowing an audit of practice and outcome over 10 years. Over the decade, the mean age of starting growth hormone treatment fell from 10.4 to 8.5 years and the starting dose increased from 0.55 to 0.95 IU/kg/week. The frequency of injections increased from three to six or seven/week. Some girls received suboptimal doses, which also differed depending on whether they were based on weight or surface area. To assess what height gain might be expected at final height, all 52 girls who were prepubertal at the start of treatment, which continued for four years or more, and who had reached final height or had a growth velocity < 2 cm/year were selected. Their mean gain in final height was 5.2 cm and the GH dose was 0.78 IU/kg/week over 5.8 years. Final height gain correlated significantly with duration of treatment, total dose received, and first year response, which itself related to starting dose. This audit shows a changing pattern of treatment over the past decade, which in many instances has been inadequate. When treatment starts before puberty and continues through to final height, with a dose of 30 IU/m(2)/week in six or seven injections, a mean increase in final height of 5 cm or more would be expected.